2016
DOI: 10.1002/anie.201609155
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Activation Modes in the Hydroboration of Aldehydes and Ketones with Germanium, Tin, and Lead Lewis Pairs

Abstract: Intramolecular germylene, stannylene, and plumbylene Lewis pairs were reacted with hexanal and yielded the cyclic addition products only with the germanium and tin reagents. In further reactivity studies, the hydroboration of aldehydes and ketones catalyzed by intramolecular germylene, stannylene, and plumbylene Lewis pairs was studied. In the case of the cyclic germylene Lewis pair, the product of the oxidative addition of pinacolborane at the germylene moiety was observed. According to stoichiometric as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
66
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(68 citation statements)
references
References 73 publications
2
66
0
Order By: Relevance
“…Since this report, main group mediated‐hydroboration reactions have gained attention over recent years and several catalytic transformations have been reported. Notable examples are the use of a β‐diketiminate supported Ga hydride for the catalytic hydroboration of CO 2 , use of Ge, Sn, Pb Lewis pairs for the hydroboration of aldehydes and ketones and the use of commercially available aluminium hydride reagents for the hydroboration of alkynes …”
Section: Non‐redox Based Catalysismentioning
confidence: 99%
“…Since this report, main group mediated‐hydroboration reactions have gained attention over recent years and several catalytic transformations have been reported. Notable examples are the use of a β‐diketiminate supported Ga hydride for the catalytic hydroboration of CO 2 , use of Ge, Sn, Pb Lewis pairs for the hydroboration of aldehydes and ketones and the use of commercially available aluminium hydride reagents for the hydroboration of alkynes …”
Section: Non‐redox Based Catalysismentioning
confidence: 99%
“…All these procedures require more or less effective catalysts based on transition-metal complexes such as Co, Fe, Ru, [15][16][17][18][19][20][21][22][23] alkaline earth metal (Mg), [24][25][26][27][28][29][30][31][32][33][34][35] but the processes culminate in frustrated Lewis pairs. [36][37][38] On the other hand, while the reduction of aryl and alkyl nitriles can be achieved using stoichiometric quantities of maingroup reducing agents such as LiAlH 4 and NaBH 4 , [39] the combustible nature of these reagents and large quantities of inorganic waste by-products they generate render the process unattractive, and hence reductive hydroboration is preferable in order to provide further functionality to the resultant amine. [40] Recently, Nakazawa et al reported the use of an ironindium complex as a catalyst for the hydroboration of aryl and alkyl nitriles, [41] while Nikonov et al introduced the Mo(IV) complex as a catalyst (5 mol %), which resulted in the hydroboration of acetonitrile and benzonitrile using the only catecholborane.…”
Section: Introductionmentioning
confidence: 99%
“…14 When compared to the transition metal catalyzed hydroboration of aldehydes and ketones which has been extensively investigated, the research on the catalytic hydroboration of carbonyl compounds using main group catalysts is less developed but has recently received considerable attention by many research groups. [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] Compared to the precious and relatively toxic transition metals, amongst the main group metals, magnesium is earthabundant, non-toxic and inexpensive. The Mg-catalyzed hydroboration has been relatively well explored and has shown high reactivity in recent studies.…”
Section: Introductionmentioning
confidence: 99%